2011
DOI: 10.1111/j.1600-0897.2011.01060.x
|View full text |Cite
|
Sign up to set email alerts
|

Ectoplacental Cone Induces Resistance to Apoptosis in High Doses of Interferon (IFN)‐γ‐Treated Decidual Cells

Abstract: PROBLEM In this study, we explored the relationship between decidual cells (DC) and interferon (IFN)-γ, in the presence or absence of ectoplacental cone (EC) using a coculture system. METHOD OF STUDY  Decidual cells and EC were isolated from pregnant mice on gestation day 7.5. DCs were cultured for 48 hr and then treated with fresh EC. After characterization, they were treated with IFN-γ, and cell death was evaluated. RESULTS  Interferon-γ drastically increased decidual apoptosis, which was partially reverted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 60 publications
(147 reference statements)
0
1
0
Order By: Relevance
“…Li et al also showed that IFN- γ could induce pregnancy failure by moderating natural killer (NK) cells [ 40 ], and it could dramatically increase decidual apoptosis [ 41 ]. In a case control study, women with extremely low birth weight infants with accepted induced spontaneous conception or assisted reproductive technology showed increased production of IFN- γ [ 42 ].…”
Section: Initial Immune Response To Dengue In Pregnant Womenmentioning
confidence: 99%
“…Li et al also showed that IFN- γ could induce pregnancy failure by moderating natural killer (NK) cells [ 40 ], and it could dramatically increase decidual apoptosis [ 41 ]. In a case control study, women with extremely low birth weight infants with accepted induced spontaneous conception or assisted reproductive technology showed increased production of IFN- γ [ 42 ].…”
Section: Initial Immune Response To Dengue In Pregnant Womenmentioning
confidence: 99%